Femme en chemise, André Derain, 1906 - André Derain (Wikimedia Commons, 1906)
Notice iconographique issue de Wikimedia Commons. Titre: Femme en chemise, André Derain, 1906. Woman in a Chemise, by André Derain. 100 x 81 cm, oil on canvas.
Droits : Licence Public domain via Wikimedia Commons
Keywords: œuvre d'art; tableau; sculpture; statue; wikimedia commons; Peintures